Characterization of an unusual black patina on the Neang Khmau temple (archaeological Khmer area, Cambodia): a multidisciplinary approach. (28th June 2016) - Casanova Municchia, A.; Bartoli, F.; Bernardini, S.; Caneva, G.; Della Ventura, G.; Ricci, M. A.; Boun Suy, T.; Sodo, A.
Abstract : In the archaeological Khmer complex (Cambodia), an unusual black patina covering both the exterior and interior walls of the Neang Khmau temple, has been observed during a recent conservative survey. In fact, it is present over all the four facades of the temple, covers a relevant part of the vertical surfaces protected from rainfall and is also homogeneously distributed on the interior of the monument. The upper and the lower areas show, on the contrary, a relevant lichen growth. The temple was built by using laterite bricks, a natural material common in tropical areas as a weathering product of pre‐existing rocks. A preliminary investigation on the patina samples together with ecological considerations excluded a biological origin of the black alteration, thus prompting a more detailed study. In this work, we have investigated the physico‐chemical origin of this unusual patina by identifying its mineralogical and chemical composition. Raman and FTIR spectroscopies, SEM‐EDS, micro‐XRF and XRPD have been applied to characterize the alteration products. Analyses have been performed both on single fragments and on polished cross sections collected from all four temple facades and from one area in the temple interior. Optical observations of the cross sections have evidenced irregularities in the thickness of the patina. Raman and FTIR spectra have revealed that the black layers are mainly composed of manganese minerals (hollandite, romanechite and manganite). This peculiar alteration pattern is interpreted as because of the tropical climatic conditions of Cambodia. Indeed the variation of wet and dry seasons favours the migration of iron and manganese ions and their successive immobilization in regions not directly subject to leaching. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In the archaeological Khmer complex (Cambodia), an unusual black patina covering both the exterior and interior walls of the Neang Khmau temple has been observed during a recent archaeological survey. Optical observations of the cross sections have evidenced irregularities in the thickness of the patina. Raman and FTIR spectra have revealed that the black layers are mainly composed of manganese minerals (hollandite, romanechite and manganite). This peculiar alteration pattern is interpreted as because of the tropical climatic conditions of Cambodia.